Spelling out the Philippine text message a descriptive study of its unique orthographic, graphic, and paralinguistic features - Santos, Ma. Lorena M. (2006)
As ubiquitous as the cell phone is in contemporary Philippine society, it is its text messaging feature that has exerted a massive social influence both in sociological and linguistic terms. In the field of language, there are questions about the effects the "conventions" that have arisen from this new medium of communication are having or will have on the use of English in the Philippines. Yet this study is more concerned with a description of the features involve its spelling shortcuts, its unconventionally used capital letters and punctuation marks, and its many emoticons. What is interesting though is that, inasmuch as brevity is the major concern in text messaging, there are patterns that emerge in the writing system of Philippine text messages, patterns which suggest that there exists a typically Filipino text spelling. This study describes the distinctive patterns of this spelling, as well as other features resulting from the nature of the cell phone medium and the Filipino user. So far, the research of other academics has focused on text messages sent to their own cellular phones. There has been no study of the many locally available and popular "text books" ? that is, books that feature collected text messages. These text books reveal much about the nature of the Philippine text message: how Filipinos spell English words in their message, how they express their identity despite the telegraphic nature of text messages, and whether the books prescribe certain spellings and usages or merely reflect the freedom and variability characteristic of text messages. Frameworks dealing with the writing system of the English language, computer-mediated communication, and the cell phone, as well as the phonological system of Philippine English, were used in this study. Lexical terms were extracted from the text books to explore how Filipinos exploit spelling and spelling variety, capitalization, punctuation marks, other graphic symbols, spacing and layout, and various emoticons to express their identity while still being brief. Also involved in this study was a comparison of the spellings of words found in Philippine text books with those in text books published in the United States and the United Kingdom. The data revealed several important points. For one thing, there are spelling patterns favored by Filipinos, namely dropped letters, phonetic spelling, and letter/number homophones. All three are attributable to the alphanumeric keypad of the cell phone as well as to the phonology of Philippine English and native language/s. For another, though Filipinos favor certain shortcuts, they also choose different vowels or consonants to drop, and spell words phonetically in different ways; variety in spelling is clearly a feature of the Philippine text message. Next, in terms of graphic and paralinguistic features, Filipinos are very creative, are fond of illustrated messages and the smiley, but do not exhibit typical Filipino usages. The comparative study revealed some very striking differences in spelling shortcuts preferred in US and UK text messages, especially with regard to rules about capital letters, acronyms, and the omission of word boundaries. Lastly, there are only suggestions and not absolute rules about how to abbreviate or combine words in these text books. However, beyond the commonality attributed to the nature of the cell phone medium and its keypad, spelling patterns of foreign and local words in text messages are noticeably different. In terms of graphic and paralinguistic features, they have more in common. The way Filipinos text reflects the influences of Filipino phonology and the native language/s and their co-existence with the English language. It can be said, then, that text messaging introduces changes and usages that are specifically suited to cell phone communication, as well as reflects the creativity and identity of the Filipino "texter." There are implications, therefore, about text message spellings as markers of regional identity and of a possible spelling dichotomy: informal versus formal spelling. Furthermore, the description of spelling Filipinisms in text messages opens up new avenues of exploration of the new varieties that this medium of communication is giving birth or will give to.